2018
DOI: 10.1002/star.201700179
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization of a Novel Thermostable Type I Pullulanase Produced Recombinantly in Bacillus subtilis

Abstract: The pullulanase gene (pulGK), encoding a thermostable type I pullulanase (PulGK), is obtained from the strain Geobacillus kaustophilus DSM7263. The gene has an open reading frame of 2157 bp that encodes a 718‐amino‐acid pullulanase, and shows the highest identity with the pullulanase from Geobacillus thermoleovorans US105. The pulGK is expressed in Bacillus subtilis WB800N using the plasmid pHT43, and the recombinant protein is secreted using the amyQ signal peptide. The level of PulGK produced in B. subtilis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Ni-NTA affinity chromatography was an appropriate method to purify this protein SI Table S3). The purified Pul GT exhibited the high specific activity of 192.56 U/mg (70 °C, pH 6.5) toward pullulan, which is obviously higher than those of the pullulanases from B. thermoleovorans US105 (3.7 U/mg, 75 °C, pH 6.0), 33 T. neapolitana (28.7 U/mg, 80 °C, pH 6.5), 17 Geobacillus kaustophilus (64.75 U/mg, 65 °C, pH 6.0), 32 and Paenibacillus barengoltzii CAU904 (68.3 U/mg, 50 °C, pH 5.5). 34 These results showed that optimizing the expression conditions and selecting appropriate purification methods could result in higher specific activity.…”
Section: ■ Results and Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Ni-NTA affinity chromatography was an appropriate method to purify this protein SI Table S3). The purified Pul GT exhibited the high specific activity of 192.56 U/mg (70 °C, pH 6.5) toward pullulan, which is obviously higher than those of the pullulanases from B. thermoleovorans US105 (3.7 U/mg, 75 °C, pH 6.0), 33 T. neapolitana (28.7 U/mg, 80 °C, pH 6.5), 17 Geobacillus kaustophilus (64.75 U/mg, 65 °C, pH 6.0), 32 and Paenibacillus barengoltzii CAU904 (68.3 U/mg, 50 °C, pH 5.5). 34 These results showed that optimizing the expression conditions and selecting appropriate purification methods could result in higher specific activity.…”
Section: ■ Results and Discussionmentioning
confidence: 85%
“…thermoleovorans US105 (3.7 U/mg, 75 °C, pH 6.0), T. neapolitana (28.7 U/mg, 80 °C, pH 6.5), Geobacillus kaustophilus (64.75 U/mg, 65 °C, pH 6.0), and Paenibacillus barengoltzii CAU904 (68.3 U/mg, 50 °C, pH 5.5) . These results showed that optimizing the expression conditions and selecting appropriate purification methods could result in higher specific activity.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Recently, to meet the multiple demands from the variety industries that makes pullulanase play diverse roles, many attempts have been made to overexpress recombinant pullulanase from alternative enzyme sources using Escherichia coli , Bacillus subtilis , or Pichia pastoris as hosts, obtained many enzymes with improved functional enzymatic properties, such as thermostable, thermo‐active, pH‐stable, detergent and chelator resistant (Kang et al, 2011; Li et al, 2018; Lu et al, 2018; Nisha & Satyanarayana, 2017; Wang et al, 2019). While, there are only a few researchers studied the high cell density fermentation of recombinant pullulanase (Duan et al, 2013; Wang et al, 2019), which is the basis of industrialization.…”
Section: Introductionmentioning
confidence: 99%